2000
DOI: 10.2135/cropsci2000.4041172x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Core Collection Approach for Identifying Resistance to Meloidogyne arenaria in Peanut

Abstract: Core collections are representative subsamples of germplasm collections. Use of core collections may improve the efficiency of germplasm evaluations by reducing the number of accessions evaluated while increasing the probability of finding genes of interest. The peanut (Arachis hypogaea L.) core collection has been examined for resistance to the peanut root‐knot nematode [Meloidogyne arenaria (Neal) Chitwood race 1]. Resistant indicator accessions from screening the core collection identified 39 clusters in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…The core collection is comprised of 831 entries selected at random (1%), at random by country of origin (26%), and by multivariate clustering of phenotypic descriptor information (73%) to minimize repetitiveness in the collection while representing the collection's genetic diversity (16,18). The peanut core collection has been previously evaluated for resistance to tomato spotted wilt virus (TSWV), Rhizoctonia limb rot, late leaf spot, peanut root knot nematode, preharvest aflatoxin contamination, early leaf spot, and Cylindrocladium black rot (2,13,16,17,19). To our knowledge, the core collection has not been previously evaluated for reaction to Sclerotinia blight.…”
mentioning
confidence: 99%
“…The core collection is comprised of 831 entries selected at random (1%), at random by country of origin (26%), and by multivariate clustering of phenotypic descriptor information (73%) to minimize repetitiveness in the collection while representing the collection's genetic diversity (16,18). The peanut core collection has been previously evaluated for resistance to tomato spotted wilt virus (TSWV), Rhizoctonia limb rot, late leaf spot, peanut root knot nematode, preharvest aflatoxin contamination, early leaf spot, and Cylindrocladium black rot (2,13,16,17,19). To our knowledge, the core collection has not been previously evaluated for reaction to Sclerotinia blight.…”
mentioning
confidence: 99%
“…We have previously reported that China appears to be valuable geographical sources of resistance to this nematode (Holbrook et al, 2000a). Second-stage screening of selected groups of accessions from the entire germplasm collection confirmed that observation (Holbrook et al, 2000b). Although peanut is not native to China, it has been cultivated widely there for several centuries (Hammons, 1982), and M. arenaria is an important pathogen of peanut in China (Minton and Baugard, 1990).…”
Section: Resultsmentioning
confidence: 56%
“…Second-stage screening of selected groups of germplasm from Japan indicated that this country is an important source for material with resistance to this pathogen (Holbrook et al, 2000b).…”
Section: Resultsmentioning
confidence: 99%
“…Second-stage testing, considering only those sets developed using the multivariate approach (Sets 4 through 8), would have resulted in the identification of one resistant accession for every eight entries examined. Holbrook et al (2000b) evaluated the effectiveness of Table 3. Efficiency of germplasm screening approaches for resistance to late leaf spot in peanut.…”
Section: Evaluation Of the Core Collection Theorymentioning
confidence: 99%